Microsign products - Vohra, Neharika, 1966- (SAGE Knowledge. Cases., 2015)
The case is about a small manufacturing company, Microsign, which has been in existence for the last thirty-five years. Microsign produces plastic fasteners, clips, clamps, and closures mainly used in electronic industries. The feature that distinguishes it and makes it special is the workforce. 50 percent of the employees at Microsign are differently-abled. The case describes how Microsign has been able to include employees with disabilities.